Effects of job stress on self-esteem, job satisfaction, and turnover intention. Issue 1 (2nd January 2016) - Yang, Hoe-Chang; Ju, Yoon-Hwang; Lee, Young-Chul
ABSTRACT: This study is focused on female inbound call center counselors who are easily exposed to emotional labor when customers express anger and hostility and use swear words toward invisible targets on the phone. Our study is based on 244 responses from female inbound call center counselors. Job stress has a significantly negative effect on job satisfaction and self-esteem. It was shown that self-esteem has a partially mediating effect, and turnover experience had a moderating effect. It is important to shed new light on the roles of self-esteem among determinants of job satisfaction.